A engenharia simultânea e o perfil da indústria de confecção da grande Natal/RN utilizando as ferramentas CAD/PDM e ERP - Lima Filho, Neil de Oliveira (2005)
This work presents the research carried through in the industrial segment of confection of clothes of the Great Natal whose objective is to show the profile, enterprise and technological management as also the use of simultaneous engineering in the development of products. The research approaches two studies. The first one presents the current picture of the companies, synthesized through twelve variable. As, through fifteen variable it shows to the level of use of Simultaneous Engineering in the Development of Products and its amplitude in relation to the Integrated Management using tools CAD, PDM and ERP (Computer Aided Design, Product Management Date, Enterprise Resource Planning). The integration of these systems acts aiming the reduction of the cost and the development time of products. The reached results indicate that simultaneous engineering is a competitive advantage and becomes possible: to reduce the life cycle of the product, to rationalize the resources, to incorporate one high standard of the quality to the process and product as well as to personalize the product to take care of the global market. It is important to note that this work also is considered to contribute for the better understanding of the real companies situation of confection located at the Great Natal and its role in the economy of the State of the Rio Grande do Norte